2022
DOI: 10.1080/20961790.2021.2002525
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Publication Output in the Field of Forensic Science and Legal Medicine using Web of Science Database from 2011 to 2020

Abstract: The aim of this study was threefold. First, it analyzed the characteristics of the publication outputs for the Legal Medicine (LM) category using the Web of Science (WoS) database during 2011–2020. Second, it discussed the distribution of the papers for the 25 most productive countries/regions in terms of quality and quantity, such as the h -index and GDP per capita . Finally, it investigated the trend and temporal stability of the journal impact factor (JIF) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…The Anglo-Saxon and Continental European countries are found to be highly productive in educational research. These findings indicated that small, well-governed countries with a long history of democracy were better at turning economic success into high-quality science, as indicated by Allik et al (2020), Öner and Orbay (2022), and Sezgin et al (2022).…”
Section: Discussionmentioning
confidence: 91%
“…The Anglo-Saxon and Continental European countries are found to be highly productive in educational research. These findings indicated that small, well-governed countries with a long history of democracy were better at turning economic success into high-quality science, as indicated by Allik et al (2020), Öner and Orbay (2022), and Sezgin et al (2022).…”
Section: Discussionmentioning
confidence: 91%
“…Los artículos publicados en revistas en la base de datos Web of Science y Scopus son aceptados en la comunidad académica como investigación de calidad, y como resultado, se utilizan con frecuencia en el análisis bibliométrico. (10) Su utilización en la investigación, aportó importantes resultados sobre la producción científica de la especialidad en Latinoamérica.…”
Section: Discussionunclassified
“…The search was conducted in a public database; therefore, no ethical approval was required. WoS is the first database to track journal quality and collect important scientific literature since 1900, with over 159 million publications [25,26]. It encompasses a vast collection of academic journals spanning diverse scientific disciplines, establishing itself as an extensive and inclusive academic information platform [27].…”
Section: Software and Datamentioning
confidence: 99%